Senior high school English reading habits and their ability to comprehend short story in English: a correlational study at SMA Negeri 1 Gunung Tuleh - Novia Santi; Delvi Wahyuni (Universitas Negeri Padang, 2020)
This study aimed to investigate senior high school students’ reading habits and their reading comprehension of short story in English. There are several categories were asked to the students in order to find out their reading habits category, the amount of reading practice, the length of time having reading habits, the types of the text read, the number of books read, the number of publish writing, the respondent of their English reading habits, the EFL students’ purpose of reading English text, the motivation of the EFL students to read English and the last the belief of EFL students about reading English. Moreover, the categories tested in reading comprehension test are main idea, finding detail information, inference, reference, and vocabulary. The participants of this research were 66 of second grade students of SMAN 1 Gunung Tuleh who took English as elective course. This study employed descriptive research. The instrumentations of this research were questionnaire and reading test. The result of this research showed that students’ reading habit is strongly influences their reading ability to comprehend short story I English. Reading habit has positive impact towards the students reading comprehension. Nevertheless, it have negative impact toward students’ reading comprehension. Key words: Reading Habits, Reading Comprehension, Short Story in English